1982
DOI: 10.1073/pnas.79.6.1930
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the gene for beta 2-microglobulin (B2m) to mouse chromosome 2.

Abstract: We have assigned the gene (B2m) coding for murine P2-microglobulin (B2M) to mouse chromosome 2 by using a novel panel ofChinese hamster-mouse somatic cell hybrid clones. Because the 35 independent primary hybrids used in this study were derived from two types of feral mice, each with a different combination of Robertsonian translocation chromosomes, as well as from mice with a normal complement of acrocentric chromosomes, analysis of 16 selected mouse enzyme markers provided data on the segregation of all 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 32 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The MyK-103 integration site maps within 11.6 centimorgans of the T-cell receptor p-chain locus with 95% confidence (46) and is positioned on the proximal half of mouse chromosome 6 (11). We also used the Bam 1.5 and the Bgl 1.6 probes to screen DNA from a panel of Chinese hamster-mouse somatic cell hybrid clones which segregated mouse chromosomes (16 (18). In transgenic mice, the foreign DNA also integrates as tandem head-to-tail arrays, as deduced by Southern blotting experiments after digestion with enzymes that cut only once within the injected DNA.…”
Section: Resultsmentioning
confidence: 99%
“…The MyK-103 integration site maps within 11.6 centimorgans of the T-cell receptor p-chain locus with 95% confidence (46) and is positioned on the proximal half of mouse chromosome 6 (11). We also used the Bam 1.5 and the Bgl 1.6 probes to screen DNA from a panel of Chinese hamster-mouse somatic cell hybrid clones which segregated mouse chromosomes (16 (18). In transgenic mice, the foreign DNA also integrates as tandem head-to-tail arrays, as deduced by Southern blotting experiments after digestion with enzymes that cut only once within the injected DNA.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3 ] The human β2M shows 70% amino acid sequence similarity to the murine protein and both of them locate on the syntenic chromosomes. [ 1 4 ] The secondary structure of β2M consists of seven β-strands which are organized into two β-sheets linked by a single disulfide bridge, presenting a classical β-sandwich typical of the immunoglobulin (Ig) domain. [ 5 6 7 ] β2M has no transmembrane region and contains a distinctive molecular structure called a constant-1 Ig superfamily domain, sharing with other adaptive immune molecules including major histocompatibility complex (MHC) class I and class II.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the B2M protein sequences of different species indicated that B2M does not show strong sequence conservation among species. The human B2M protein shares 70% sequential identity with that of mice [ 33 ]. Furthermore, interestingly, no intraspecific genetic polymorphisms have been observed in human B2M [ 34 ], suggesting that changes in the B2M protein sequence could be undesirable to the host.…”
Section: Introductionmentioning
confidence: 99%